2022
DOI: 10.1161/hypertensionaha.121.16492
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Blood Pressure and Salt Balance By Pendrin-Positive Intercalated Cells: Donald Seldin Lecture 2020

Abstract: Intercalated cells make up about a third of all cells within the connecting tubule and the collecting duct and are subclassified as type A, type B and non-A, non-B based on the subcellular distribution of the H + -ATPase, which dictates whether it secretes H + or HCO 3 − . Type B intercalated cells mediate Cl − absorption and HCO 3 − secretion, which occurs largely thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 117 publications
0
8
0
Order By: Relevance
“…The b-ICs of the cortical collecting duct control acid-base balance and also modulate our body fluid volume. 45 In addition to the SCTR, pendrin (SLC26A4), and CFTR, several other membrane proteins seem to have key roles in mediating/regulating urinary base excretion. The SLC4A9 (AE4) transporter, a suggested Na 1 -coupled HCO 3 2 transporter, was recently identified to play a critical role in regulation of pendrin function and to permit increases in renal base excretion 46 In addition, also the IRR is strongly expressed in the b-ICs and has an important role in regulating urine base excretion.…”
Section: Discussionmentioning
confidence: 99%
“…The b-ICs of the cortical collecting duct control acid-base balance and also modulate our body fluid volume. 45 In addition to the SCTR, pendrin (SLC26A4), and CFTR, several other membrane proteins seem to have key roles in mediating/regulating urinary base excretion. The SLC4A9 (AE4) transporter, a suggested Na 1 -coupled HCO 3 2 transporter, was recently identified to play a critical role in regulation of pendrin function and to permit increases in renal base excretion 46 In addition, also the IRR is strongly expressed in the b-ICs and has an important role in regulating urine base excretion.…”
Section: Discussionmentioning
confidence: 99%
“…11 Similarly, our findings highlight the predominant role of non–type A ICs in maintaining water and NaCl homeostasis. 11,5557 The reduction in pendrin expression together with the likely defect in H + -ATPase activity as seen in the DOCA/HCO 3 − model explains the more pronounced alkalosis. Although extremely rare, the association of severe alkalosis with primary dRTA or Pendred syndrome has been reported in infants treated with thiazide diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study has shown that, in the late distal convoluted tubules, ENaC is likely regulated by glucocorticoids [58]. Therefore, intricate and coordinated actions of MR-dependent and -independent signaling optimize NaCl transport mechanisms in the distal nephron, thereby precisely controlling salt handling in the segment [52,59,60].…”
Section: Electrolyte Handling In Renal Tubulesmentioning
confidence: 99%